2019
DOI: 10.12659/msm.916009
|View full text |Cite
|
Sign up to set email alerts
|

Combined Signature of the Fecal Microbiome and Plasma Metabolome in Patients with Ulcerative Colitis

Abstract: Background Ulcerative colitis is a chronic, idiopathic inflammatory disease that destroys the colon structure. Nevertheless, the exact pathogenesis is not clear and needs to be fully elucidated. Material/Methods Stool and plasma samples were used for 16S ribosomal RNA sequencing and liquid chromatography mass spectrometry, respectively. In addition, we detected the level of trimethylamine N-oxide. Finally, we performed Pearson correlation analysis between the microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…However, prior IBD microbiome studies have mostly included subjects with an established treatment; of the 143 microbiome studies included herein, only 11 included treatment-naïve patients [ 15 , 66 , 69 , 75 , 81 , 84 , 87 , 93 , 117 , 118 , 123 ], sometimes only on a small subset of the cohort, and only one was conducted prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, prior IBD microbiome studies have mostly included subjects with an established treatment; of the 143 microbiome studies included herein, only 11 included treatment-naïve patients [ 15 , 66 , 69 , 75 , 81 , 84 , 87 , 93 , 117 , 118 , 123 ], sometimes only on a small subset of the cohort, and only one was conducted prospectively.…”
Section: Resultsmentioning
confidence: 99%
“…The fecal microbiome has been compared to the plasma metabolome in disease states such as ulcerative colitis where products of sphingolipid metabolism, specifically sphingosine 1phosphate in the blood correlate with Roseburia, Klebsiella, and Escherichia-Shigella 72 .…”
Section: Discussionmentioning
confidence: 99%
“…The important role of gut microbiota in UC has been widely accepted, and disruptions to the microbiome have been implicated in the pathogenesis ( Derikx et al, 2016 ). A recent study of fecal microbiota analysis revealed that the relative abundance of Escherichia-shigella and Streptococcus was elevated, whereas Bacteroides and Prevotella_9 was reduced in UC patients compared to healthy participants ( Sun et al, 2019 ). Another study reported the gut microbial dysbiosis in Chinese inflammatory bowel disease patients, and found that the community of Megamonas and Butyricicoccus , which could produce short-chain fatty acids and modulate colonic regulatory T cells, was significantly repressed in UC patients stool samples ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%